Effect of carbon nanotube buckypapers on interlaminar fracture toughness of thermoplastic composites subjected to fatigue tests - de Paula Santos, Luis Felipe [UNESP]; Monticeli, Francisco Maciel; Ribeiro, Bruno; Costa, Michelle Leali [UNESP]; Alderliesten, René; Botelho, Edson Cocchieri [UNESP] (Elsevier, 2025)
Three-phase composites, especially those composed of high performance thermoplastics, have not been properly investigated with respect to their interlaminar fracture toughness. Therefore, this study investigates effect on the interlaminar fracture toughness by adding carbon nanotube buckypaper (BP), tested under cyclic loading in mode I and II. BP weakened the interlaminar fracture toughness in mode I, creating an easy path for crack growth and reducing the strain energy release (SERR) values in the Paris curves. Conversely, under mode II BPs presented no significant influence to the interlaminar fracture toughness and fatigue life; however, a slight improvement was observed due to the bridging effect. The energy balance principle model for opening delamination showed that BP composites require less energy per unit of area to crack growth, resulting in a smoother fracture surface with fewer failure mechanisms. In contrast, BP slightly increased the energy per unit of area for crack growth, leading to a rougher fracture surface with a higher prevalence of failure mechanisms under mode II. This work underscores the importance of examining the individual effects of mode I and II loadings on BP laminates since these interleaves affect the interlaminar toughness and fatigue life differently.
Keywords: Buckypapers; Fatigue behavior; Fractography; Interlaminar fracture toughness; Thermoplastic composites